Effects of fixed labial and lingual orthodontic appliances on speech sound production: A comparative in vivo study - Danish Intesaab, Ahmed; Ajit, Kalia; Salil, Nene; Juhi, Joshi; Girija, Adsure (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2019)
Introduction: The eventual esthetic solution for patients who do not want visible orthodontic appliance is the lingual orthodontic appliance. The result produced by the lingual orthodontic appliance is parallel to those produced by the labial orthodontic appliance. However, there is an articulation problem due to the position of the lingual brackets as there is a modification of the lingual surface of the teeth. Speech problems with each appliance are studied individually and extensively, but the comparison of both appliances regarding speech is very scanty. Aim: The aim of this study is to evaluate the effect of fixed labial and lingual orthodontic appliance on speech sound production at a different time interval. Materials and methods: A total number of 30 patients were included in this study, 15 patients were bonded with the fixed labial appliance (Group 1) and 15 patients were bonded with the fixed self-ligating lingual appliance (Group 2). Based on four types of errors (E1, E2, E3, E4), a total of nine groups of sounds (S1, S2, S3, S4, S5, S6, S7, S8, S9) were evaluated for each audiovisual sample at four different time intervals (T1, T2, T3, T4) by two different speech therapist individually in each group. Results: A high degree of agreement was found between the two observers in both groups regarding the type of sound effected and the type of error during sound production. The total number of patients with effected speech is more in the lingual group compared to the labial group on the same day of bonding until six months in treatment.Conclusion: The results of the present study demonstrated the following, the total number of patients with lingual appliance had more errors in speech compared to the labial appliance at the beginning of the treatment. Patients with lingual appliance required more time for adaptation concerning speech. A similar group of sounds was effected in both types of an appliance with a similar type of error. Patients with labial appliance showed more comfort and easier adaptation with the appliance. The anatomical location of the appliance plays an important role in speech alteration and adaptation. These findings should be considered before selecting an appliance for a particular patient.